Recent Advanced Endoscopic Management of Endoscopic Retrograde Cholangiopancreatography Related Duodenal Perforations - Seon Mee Park (Korean Society of Gastrointestinal Endoscopy, 2016)
The management strategy for endoscopic retrograde cholangiopancreatography-related duodenal perforation can be determined based on the site and extent of injury, the patient's condition, and time to diagnosis. Most cases of perivaterian or bile duct perforation can be managed with a biliary stent or nasobiliary drainage. Duodenal wall perforations had been treated with immediate surgical repair. However, with the development of endoscopic devices and techniques, endoscopic closure has been reported to be a safe and effective treatment that uses through-the-scope clips, ligation band, fibrin glue, endoclips and endoloops, an over-the-scope clipping device, suturing devices, covering luminal stents, and open-pore film drainage. Endoscopic therapy could be instituted in selected patients in whom perforation was identified early or during the procedure. Early diagnosis, proper conservative management, and effective endoscopic closure are required for favorable outcomes of non-surgical management. If endoscopic treatment fails, or in the cases of clinical deterioration, prompt surgical management should be considered.